Studi Literatur Literasi Sains di Sekolah Dasar - Nofriza Efendi; Nelvianti; Refli Surya Barkara (Jurnal Dharma PGSD, 2021)
The problems in this study are related to the application of scientific literacy in elementary Schools and constraints in its application. This study uses literature studies from previous research articles. Data search was carried out by doing a search on Google Scholar or Google Scholar with the keyword science literacy in elementary schools. From the search results, it was found that 20 journal articles and proceedings met the criteria. The results showed that the application of scientific literacy in primary schools is in line with the 4 pillars of UNESCO education and is applied through approaches, models or learning methods that are compatible with science learning. The obstacles faced in its application are demanding the ability of students and teachers, students who have not been able to think critically and teachers who do not know how to apply it properly and correctly.